The Double Calcaneal Osteotomy for Pediatric Flatfoot. Issue 4 (November 2022) - Kothari, Ezan A.; Young, Sean M.; Gilbert, Shawn; Conklin, Michael J.
Category: Hindfoot Introduction/Purpose: The double calcaneal osteotomy combines a medial calcaneal sliding osteotomy and lateral column lengthening. Corrective osteotomies, as opposed to arthrodesis and arthroereises, are preferred for foot deformity correction in children and adolescents because they preserve joint mobility, shock absorption, and avoid concerns about adjacent joint degeneration. Individually, both types of osteotomies have demonstrated efficacy in achieving deformity correction and improved functional outcomes for patients. The literature regarding outcomes of this procedure in children is sparse. This retrospective study objectively analyzes outcomes of children who underwent double calcaneal osteotomies at our institution by comparing pre and postoperative radiographs and reporting postoperative complications. To our knowledge, this study contains the largest sample size of symptomatic flatfeet analyzed with regards to double calcaneal osteotomies in children. Methods: Patients who underwent a double calcaneal osteotomy over the past 5 years at our institution were analyzed. Pre and postoperative weightbearing radiographs of the foot were measured (Figure 1). Paired t tests were used to compare pre and postoperative measurements. Statistical significance was set at α < 0.05. Additional factors analyzed for each procedure include total operative time, torniquet time, hardware used for fixation, type of graft, concomitant procedures, and post-operative complications such as infection, nerve injury, nonunion, and reoperation. Results: A total of 20 patients and 26 feet were studied. Significant correction from pre to postoperative radiographic measurement was noted for the talo-first metatarsal angle, talonavicular coverage angle, calcaneal pitch, and tibiocalcaneal angle (p < 0.001). Complications were noted in 3 of the 20 patients, or 3 of 26 feet, and included infection, painful hardware, and hardware failure. Conclusion: The double calcaneal osteotomy was found to be effective in correcting the radiographic parameters associated with flatfoot deformity in children and adolescents with symptomatic flatfeet. The average postoperative radiographic measurements for the 26 feet analyzed were significantly improved from preoperative measurements. Pediatric orthopedists should strongly consider the double calcaneal osteotomy for appropriate surgical candidates.